Effects of aluminum, iron and/or low pH on rice seedlings grown in solution culture - Jamaludin, Alia Farhana; Jusop, Shamshuddin; Ishak, Che Fauziah; Mohd Hanif, Ahmad Husni; Panhwar, Qurban Ali (Friends Science Publishers, 2015)
Water in the paddy field covered by acid sulfate soils having very low pH contains high amount of Al and Fe that affects rice growth. A laboratory study was conducted to qualify rice grown under the adverse conditions can withstand the stresses. Two rice varieties, MR 219 and MR 253, were grown hydroponically at various pH (3, 4, 5, 6, 7), Al (0, 20, 40, 60, 80, 100 µM) and Fe (0, 20, 40, 60, 80, 100 µM) concentrations. After 14 days, rice root length and surface area were determined using a root scanner. Thereafter, organic acids released by the roots of rice were determined by high performance liquid chromatography. Results showed that the root length decreased with increasing Al and/or Fe concentration. On the contrary, the root length increased linearly as the pH of the solution increased. This phenomenon was probably in part related to the exudation of oxalic, citric and malic acids by the rice roots. It was observed that the amount of organic acids released was increased with increasing Al and/or Fe concentration in the solution culture. Hence, it is believed that these organic acids were responsible for chelating some of the Al and/or Fe in the solution, rendering them unavailable for their uptake by rice. In this way, rice plants can withstand some degree of Al3+ and/or Fe2+ toxicity.